Disaster Preparedness Among Hospital Nurses in a High-Risk Region: A Cross-Sectional Study from Pekalongan, Indonesia - Fauzan, Ahmad; Mustikawati, Neti; Susri Utami (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Disaster preparedness is an essential component of healthcare systems, particularly in high-risk regions where healthcare providers, especially nurses, are expected to respond effectively during emergencies. Their readiness depends on sufficient training, knowledge, and confidence to act under pressure. Objective : This study aimed to assess the level of disaster preparedness among nurses working at RSI PKU Muhammadiyah Pekajangan, a hospital located in a disaster-prone area of Pekalongan, Indonesia. Methods: A descriptive cross-sectional study design was applied, involving 142 nurses selected through total population sampling. Data were gathered using the Disaster Preparedness Evaluation Tool (DPET), which consists of 28 items covering four core domains. Descriptive statistics were used to analyze demographic information and preparedness levels. Results: Among the respondents, 69.7% were women, and 60.6% held a Diploma III in Nursing. The majority (62.0%) were assigned to inpatient care units. Participants had an average of 10.09 years of professional experience, ranging from 1 to 34 years. Preparedness levels were classified as moderate in 64.1% of nurses and good in 35.9%; no respondents fell into the low-preparedness category. Conclusion: Most nurses demonstrated a moderate level of disaster preparedness, regardless of their educational background or years of experience. To enhance hospital readiness, it is recommended that continuous training, simulation exercises, and regular evaluations be integrated into institutional disaster management strategies.